Immunosensor for prostate-specific antigen using Au/Pd@flower-like SnO2 as platform and Au@mesoporous carbon as signal amplification1. Issue 90 (2nd October 2015) - Yang, Long; Zhao, Hui; Deng, Guogang; Ran, Xin; Li, Yucong; Xie, Xiaoguang; Li, Can-Peng
<x xml:space="preserve">Abstract</x> The illustration for the constructed electrochemical immunosensor and the signal amplification strategy.